ART integration in oral health care systems in Latin American countries as perceived by directors of oral health - Oswaldo Ruiz; Jo E. Frencken (University of São Paulo, 2009)
The aim of this study was to carry out a situation analysis of: a) prevalence of ART training courses; b) integration of ART into the oral healthcare systems and; c) strengths and weaknesses of ART integration, in Latin American countries. MATERIALS AND METHODS: A structured questionnaire, consisting of 18 questions, was emailed to directors of national or regional oral health departments of all Latin American countries and the USA. For two countries that had not responded after 4 weeks, the questionnaire was sent to the Dean of each local Dental School. The questions were related to ART training courses, integration of ART in the dental curriculum and the oral healthcare system, barriers to ART implementation in the public health system and recommendations for ART implementation in the services. Factor analysis was used to construct one factor in the barrier-related question. Means and percentages were calculated. RESULTS: The response rate, covering 55% of all Latin American countries, was 76%. An ART training course had been given in all Latin American countries that responded, with more than 2 having been conducted in 64.7% of the respondent countries. ART was implemented in public oral health services in 94.7 % of the countries, according to the respondents. In 15.8% of the countries, ART was applied throughout the country and in 68.4%, in some areas or regions of a country. ART had been used for more, or less, than three years in 42.1% and 47.4% of the countries, respectively. Evaluation and monitoring activities to determine the effectiveness of ART restorations and ART sealants had been carried out in 42.1% of the countries, while evaluation training courses had taken place in only 3 countries (15.8%). Respondents perceived the "increase in the number of treated patients" as the major benefit of ART implementation in public oral health services. The major perceived barrier factors to ART implementation were "operator opinion" and "high patient load", followed by "lack in supplies of materials and instruments and operators" and "lack of ART training". Respondents recommended that the number of ART courses should be increased. CONCLUSIONS: The introduction of ART into the public oral health systems in Latin American countries has taken place but is still in its infancy. More ART training courses need to be organized if the approach is to be adopted in oral health service systems in these countries.